Answer :

Take L.H.S.










{sin (-A) = -sin A & cos (-A) = cos A}









= cot C


= R.H.S.


Hence Proved


ii. Take L.H.S.:


sin(B– C)cos(A – D) + sin(C – A)cos(B – D) + sin(A – B)cos(C – D)


Multiplying & Dividing by 2:



{ 2 sin A cos B = sin (A + B) + sin (A – B)}






{sin (-A) = -sin A}




= 0


= R.H.S.


Hence Proved


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove that :
<
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that :
<
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics